2022
DOI: 10.1021/acsanm.2c02660
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework-Derived LaFeO3@SnO2/Ag p–n Heterojunction Nanostructures for Formaldehyde Detection

Abstract: Using n-type and p-type semiconductor materials to construct p–n heterostructures has proven effective for improving gas-sensing properties. In this study, we synthesized the nanocomposites of SnO2 derived from a metal–organic framework (MOF) and LaFeO3 by loading atomic silver on its surface. The response value (R a/R g) of the nanocomposites to 10 ppm formaldehyde reached 498 at 140 °C, but they showed almost no response to 50 ppm interference volatile organic compounds (VOCs), and the response–recovery time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The XRD patterns of SA, CA, and g-C3N4 samples are shown in Figs. 2(a 112), ( 022), ( 004), ( 204), (040), and (116) crystal planes of orthorhombic LaFeO3 (PDF#74-2203) [22], demonstrating the excellent crystallinity of samples. With the addition of the AgNO3 standard solution, peaks at 38.12 o and 44.30 o emerge obviously, which correspond to the (111) and ( 200) crystal facets of Ag (PDF#04-0783) [23].…”
Section: Characterization Resultsmentioning
confidence: 94%
“…The XRD patterns of SA, CA, and g-C3N4 samples are shown in Figs. 2(a 112), ( 022), ( 004), ( 204), (040), and (116) crystal planes of orthorhombic LaFeO3 (PDF#74-2203) [22], demonstrating the excellent crystallinity of samples. With the addition of the AgNO3 standard solution, peaks at 38.12 o and 44.30 o emerge obviously, which correspond to the (111) and ( 200) crystal facets of Ag (PDF#04-0783) [23].…”
Section: Characterization Resultsmentioning
confidence: 94%
“…The reduction of resistance can be attributed to the dissociation of a small amount of H 2 O molecules on the surface of the LFS microspheres, and the dissociated electrons enter the LFS through the carrier channel to combine with holes, resulting in a decrease in the overall resistance of the sensor (eq ). The decrease in the sensor’s response value is attributed to the fact that H 2 O molecules occupy part of the active sites . Because the working temperature of the LFS sensor is much higher than the boiling point of water, the probability of water molecules being adsorbed on the sensor electrode is greatly reduced, and the moisture resistance of the sensor is improved (Figure S4e).…”
Section: Resultsmentioning
confidence: 97%
“…36 The decrease in the sensor's response value is attributed to the fact that H 2 O molecules occupy part of the active sites. 37 Because the working temperature of the LFS sensor is much higher than the boiling point of water, the probability of water molecules being adsorbed on the sensor electrode is greatly reduced, and the moisture resistance of the sensor is improved (Figure S4e).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In recent years, LaFeO 3 has been considered as a typical p-type perovskite-type oxide due to its relatively simple preparation, highly stable structure, and excellent thermal stability [16,17]. Previous studies have shown that LaFeO 3 exhibits good gas sensitivity towards gases such as ethanol, acetone, and formaldehyde [18].…”
Section: Introductionmentioning
confidence: 99%